Beyond social democracy and neo-liberalism: Towards a social economy - Malcolm C. Sawyer (PSL Quarterly Review, 2021)
The paper brings together a range of ideas on the construction and nature of what may be termed a post neo-liberal social economy. The social democratic era of the early post-war decades and the neo-liberal era of the past four decades are briefly considered. Some general thoughts on the mechanisms of economic co-ordination under the heading of markets, networks and planning are provided. The roles of different forms of ownership and control - private, public, mutual and co-operative - in a social economy are then considered. The strategic roles to be played by the State under the heading of social economic strategy are next considered. The final main section relates to the role of the State: welfare and income support, and macroeconomic policies.
Keywords: H4; L52; P11; P41; 330; Markets; varieties of ownership forms; social economic strategy; neo-liberalism